Status and Utility of Pearl Millet Germplasm for Crop Improvement - Vetriventhan, Mani; Kumar, Vinod; Dagunapur, Naresh Reddy; Srinivas, Raja; Jagadeesh, Kommineni; Kanchanapally, Anilkumar; Peerzada, Ovais; Elangovan, M.; Venkatesh K.; Singh, Kuldeep (Springer, 2024)
Millets assume greater importance in the context of changing climate and increasing demand for highly nutritious food and animal feed. The plant genetic resources are of greater value for crop improvement, which is essential in meeting future demands of food security and nutrition. Pearl millet is a climate-resilient and nutrient-dense crop enriched with a huge germplasm diversity that holds massive potential for crop improvement in the form of several unexplored genes for various traits. Globally, several genebanks together conserve over 73,000 pearl millet germplasms including wild and weedy relatives. The ICRISAT Genebank conserves the largest collection of Pennisetum spp. germplasm (24,663 accessions, originating from 51 countries). The characterisation and evaluation of the existing germplasm can unveil the trait diversity and can result in the identification of trait-specific sources. Several trait-specific sources identified for various biotic and abiotic stress resistance and quality traits can improve the utility of pearl millet germplasm for crop improvement. This chapter describes the status of pearl millet germplasm conservation ex situ and in situ, promising trait-specific sources for various biotic and abiotic traits and their utilisation in crop improvement.